2011
DOI: 10.1246/cl.2011.699
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Characterization of Self-assembled Peptide Nanostructures toward Peptide-directed Biomineralization

Abstract: There is increasing interest in nanostructures and in the molecular design of building blocks which self-assemble into nanoscaled intelligent materials. We outline a method for controlling the nanostructures of amphiphilic nonapeptides by changing the pH of the aqueous medium. A lysine residue on the hydrophilic face of the peptide plays a critical role as a morphology-control unit. This self-assembling peptide may, therefore, find application as a template for peptide-directed biomineralization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…We previously designed and synthesized a series of amphiphilic β-sheet-forming nonapeptides and showed that they self-assemble to form nanofibers at relatively low peptide concentrations of ∼100 μM in water. The use of water avoids potential metal/salt contamination by buffer solutions. Our results demonstrated that short peptides hold potential for practical applications and encouraged us to employ them as templates to align ZnO nanocrystals along self-assembled peptide nanostructures. Peptides provide significant advantages in structural diversity and manipulation of template molecules compared to small (e.g., amino acids) and large (e.g., proteins) biomolecules.…”
Section: Introductionmentioning
confidence: 87%
“…We previously designed and synthesized a series of amphiphilic β-sheet-forming nonapeptides and showed that they self-assemble to form nanofibers at relatively low peptide concentrations of ∼100 μM in water. The use of water avoids potential metal/salt contamination by buffer solutions. Our results demonstrated that short peptides hold potential for practical applications and encouraged us to employ them as templates to align ZnO nanocrystals along self-assembled peptide nanostructures. Peptides provide significant advantages in structural diversity and manipulation of template molecules compared to small (e.g., amino acids) and large (e.g., proteins) biomolecules.…”
Section: Introductionmentioning
confidence: 87%
“…Therefore, SAPs are highly versatile structural and functional molecules. To date, many designed SAPs have been reported, [5][6][7][8][9][10][11] and most of these SAPs are roughly divided into three classes: b-sheet peptides, a-helix peptides and peptide amphiphiles.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] The use of short peptides at lower concentrations has potential for practical applications due to its facile and inexpensive preparation on a commercial scale. Here, we describe the biomimetic synthesis of silica nanofibers by using self-assembled peptide nanostructures as templates (Fig.…”
Section: Introductionmentioning
confidence: 99%